Formulation of Air Freshener Gel Combination of Mint Leaf Essential Oil (Mentha piperita L.) and Lemon (Citrus limon (L) Burm F.) - Hafidzah, Nurul; Putri, Novita Eka Kartab; Almeida, Maria; Rusman, Arman; Herman, Herman (Journal of Pharmaceuticals and Natural Sciences, 2024)
Air freshener gel is a semi-solid fragrance product that uses carrageenan and pectin as gel-forming components to overcome unpleasant odors when in a room with high temperatures. The purpose of this study was to determine the composition of carrageenan and pectin as gel-forming materials for air fresheners and the composition of the aroma comparison of mint oil (Mentha piperita L.) and lemon (Citrus limon (L) Burm F). The gel base was made with a ratio of carrageenan: pectin concentration of 1: 2; 1.8: 1.2; 2.5: 0.5 then the base was evaluated including organoleptic examination, stability test and gel hardness. The best base was then added with mint oil and lemon with a ratio of 1: 1.5; 1.25: 1.25; 1.5: 1 and the gel preparation was evaluated with organoleptic parameters, gel stability, gel hardness, liquid evaporation, fragrance resistance and hedonic test. The results of the study showed that the best base preparation after the evaluation of the base was a ratio of carrageenan: pectin concentration of 25: 0.5. Evaluation of the preparation with the addition of mint leaf oil (Mentha piperita L.) and lemon (Citrus limon (L) Burm F) to the base showed a value that was not too significant in the evaluation results. In the hedonic test, the formula with the addition of 2.5%: 2.5% mint leaf oil (Mentha piperita L.) and lemon (Citrus limon (L) Burm F) was the formula preferred by the panelists. So it can be concluded that the carrageenan and pectin combination room freshener gel with a concentration ratio of 2.5: 0.5% can be formulated as a base for room freshener gel preparations, namely producing a chewy and elastic gel base. The formulation of the most preferred combination of mint leaf essential oil and lemon oil as a gel fragrance is with a concentration of 2.5: 2.5%, because it produces a refreshing aroma